PELAKSANAAN TUGAS PEMBIMBING KEMASYARAKATAN DALAM PROSES DIVERSI ANAK YANG BERKONFLIK DENGAN HUKUM DI BALAI PEMASYARAKATAN KELAS I MEDAN - Ica Karina; Madiasa Ablisar; Muhammad Hamdan; Marlina Marlina (Universitas Sumatera Utara, 2018)
ABSTRACT A Community Guidance is a correctional officer at the Correctional Institution conducting guidance to a Penitentiary Sub-prisoner outside the authority of LAPAS. In the juvenile justice process, the community counselor is tasked with preparing a community research report (LITMAS). This social research serves to find out more in the background of children's social life both economic, educational, religious and social interaction. Form of guidance given in the form of: religious education, character education, guidance and counseling of individuals and groups, formal education, scouting, vocational education, psychotherapy, literature, and psychiatry therapy. The Criminal Function is no longer merely a jail but it is also a process of rehabilitation and social reintegration of the Insured Citizens within the penitentiary. This study aims to find out the task of social guidance against children who are faced with the law and to know the implementation of the social guidance in the process of diversion against the children who are faced with the law in the Class I Pemasyarakatan Medan. This research indicates that the task of the Community Guidance in the making of community research and mentoring of children in conflict with the law as the suspect / defendant in the criminal justice process of the child, and for the adult suspects in certain crimes and LITMAS for the interest of prisoners' care and guidance of the prison shows the involvement of the Community Guidance Counselor since the beginning of the legal process until the return of a prisoner and prison student to the public. In the execution of a Class 1 Medan community mentor has the duties and functions, among others, the basic task of the first class BAC supervisor Medan is to provide community guidance or alleviation of children in accordance with applicable legislation and conduct coaching, guidance and supervision of clients outside Penitentiary . Keywords: Task Implementation, Community Guidance.